Toward low-carbon cities: a review of circular economy integration in urban waste management and its impact on carbon emissions - Haris, Nur Izzah Nabilah; Al Edrus, Syeed SaifulAzry Osman; Abdul Raof, Nurliyana; Wondi, Mohd Hafizz; Khan, Waseem Razzaq; Sien, Leong Sui; Ilyas, R. A.; Norrrahim, Mohd Nor Faiz; Sawatdeenarunat, Chayanon (John Wiley and Sons, 2024)
Urban areas significantly contribute to global carbon emissions, necessitating a shift toward low-carbon environments. The concept of low-carbon cities presents a viable pathway for mitigating these anthropogenic emissions, particularly through solid waste management. This article explores the critical role of circular economy-integrated waste management (CEWM) strategies in reducing carbon emissions and fostering sustainable urban development. We examine city-level CEWM initiatives worldwide, assess the carbon emission quantification methods, and highlight specific CEWM strategies with significant carbon reduction potential. Our findings reveal that city-level initiatives predominantly prioritize waste reduction and prevention (51%), followed by education and engagement (23%), material recycling and upcycling (21%), and waste conversion (6%). Key strategies such as composting, waste sorting, recycling, and biogas plants have demonstrated substantial potential in reducing carbon emissions. Integrating CE principles with waste management transforms the traditional linear take-make-dispose model into a circular approach that minimizes waste and maximizes resource efficiency. This integration is crucial for reducing carbon emissions and promoting a sustainable urban environment. A holistic perspective is required to plan and strategize for sustainable urbanization whereby CE and waste management are interconnected. CE principles provide an ideal foundation that enhances waste management strategies toward sustainability, ultimately leading to reduced carbon emissions. This article provides essential insights to equip decision-makers with evidence-based strategies for effective urban waste management.